2019
DOI: 10.1101/609040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional Profiling of Single CRISPR/Cas9-Edited Human Long-Term Hematopoietic Stem Cells

Abstract: and Eric R. Lechman (elechman@uhnresearch.ca) regenerative therapies. Thus, LT-HSCs are essential for therapeutic genome editing to correct acquired and genetic hematopoietic disorders 3,4 . Furthermore, the pathogenesis of hematological malignancies like acute myeloid leukemia (AML) is associated with the presence of initiating mutations acquired in LT-HSCs, which lead to their competitive expansion 5,6 . Pre-leukemic LT-HSCs are a source of clonal evolution within blood malignancies and can act as a reservoi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…However, there was a reduction in the percentage of chimeric cells at 12 weeks post-transplantation in the RNP+AAV group, which was consistent with the results of other studies and may reflect a reduced engraftment capacity of edited mixed cells [16,17]. The reason that the engraftment capacity of edited mixed HSPCs is decreased compared with that of unedited cells may be that the HDR donors are themselves toxic or that HSCs are intrinsically more di cult to edit than other cells [28]. We further demonstrated that GFP+HSPCs representing the gene-targeted HSPCs can be detected in the BM of NSI mice, which indicated that some of the targeted HSPCs were stable for up to 12 weeks post-transplantation, although the in vivo genetargeted HSPCs had a nearly 6-fold reduction compared with the in vitro gene-targeted HSPCs.…”
Section: Discussionsupporting
confidence: 85%
“…However, there was a reduction in the percentage of chimeric cells at 12 weeks post-transplantation in the RNP+AAV group, which was consistent with the results of other studies and may reflect a reduced engraftment capacity of edited mixed cells [16,17]. The reason that the engraftment capacity of edited mixed HSPCs is decreased compared with that of unedited cells may be that the HDR donors are themselves toxic or that HSCs are intrinsically more di cult to edit than other cells [28]. We further demonstrated that GFP+HSPCs representing the gene-targeted HSPCs can be detected in the BM of NSI mice, which indicated that some of the targeted HSPCs were stable for up to 12 weeks post-transplantation, although the in vivo genetargeted HSPCs had a nearly 6-fold reduction compared with the in vitro gene-targeted HSPCs.…”
Section: Discussionsupporting
confidence: 85%
“…As the seed cells for the blood system, their clinical potential for cellular therapies is vast and the need to understand their molecular program in different physiological states is critical for their therapeutic application. Recently, cell culture conditions have been reported to produce large numbers of functional mouse and human HSCs (hHSCs) ( Fares et al., 2017 ; Wilkinson et al., 2019 ) but, in all cases, the substantial majority of cells produced are non-HSCs ( Bak et al., 2018 ; Gundry et al., 2016 ; Shepherd and Kent, 2019 ; Wagenblast et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…As an additional (LT-)HSC marker CD133 was introduced, and for both CD34 and CD133 clinical largescale isolation technologies are available, but CD133+ selected cells featured superior ex vivo proliferation potential compared to CD34+ selected cells [38,42], and CD133 was successfully used as entry receptor for lentiviral gene transfer into LT-HSCs [38]. Their sustainable repopulation potential suggests LT-HSCs as a prime target cell type for gene therapies [43]. Further, CD45RA expression was found to distinguish multipotent (CD133+ CD34+ CD45RA−) from lympho-myeloid (CD133+ CD34+ CD45RA+) human HPC fractions [44].…”
Section: Heterogeneity Of Hematopoietic Stem and Progenitor Cellsmentioning
confidence: 99%
“…To address these issues it might be useful to assess the genetic modifications for each cell type being present in the graft, and/or to develop manufacture concepts that target a specific cell type. In fact, high efficiency human LT-HSCs gene editing using CRISPR/Cas9 technology was recently reported [43].…”
Section: Heterogeneity Of Hematopoietic Stem and Progenitor Cellsmentioning
confidence: 99%